Corporate venturing in times of crisis: securing resources through legitimacy - Stefanie Weniger; Svenja Jarchow (Review of Managerial Science, 2024)
Accelerating innovation and creating new businesses have become a top priority for today's firms. Various corporate venturing (CV) modes have helped them achieve this goal. Yet, scholars and practitioners have noted the dynamic nature of CV initiatives that compete with other strategic initiatives for organizational resources and top management support. The fear that CV units face drastic cuts in times of crisis seems reasonable. To shed light on the resource dynamics and the CV units' responsive actions, we conducted an abductive study with 16 CV units to analyze the CV units' response to the COVID-19 crisis that transformed the world in the spring of 2020. Our findings show that an external crisis can unsettle a CV unit's internal legitimacy. In the adaption processes observed, we identify four different legitimacy-seeking mechanisms– adjusting, sensing, focusing, and mobilizing –used by the CV units to secure resources, support, and goodwill from relevant internal stakeholders. The mechanisms uncovered differ from previously studied strategies as they emphasize the dynamic nature of legitimation efforts. The mechanisms used are affected by the perceived organizational distress caused by the crisis and the CV unit's pre-crisis legitimacy. Drawing on the critical role played by legitimacy in resource allocation decisions, this study allows us to better understand theoretically and practically how CV is embedded in organizational settings and how CV units can preserve internal (financial) resources.
Keywords: L26; O31; O32; 650; Corporate venturing; Crisis response; Legitimacy; Resource allocation